Aplikasi Pembelajaran Asas Subjek Konsep Pengaturcaraan Berorientasikan Objek - Mohd Esa, Siti Aisyah; Mohd Nawi, Nazri (Applied Information Technology And Computer Science, 2021)
The learning application for the basic subject of object-oriented programming concept is an application that is developed to help the students and citizens by learning from notes and test to understand the basic subject of object-oriented programming. In this new era of technology, most of the teaching and learning process are using online learning. However, the applications for these subject is hard to find in any market. The user also lost interest to make it as their source or reference. By looking at those weaknesses, a learning application is developed by using the e-learning concept. E-learning is a learning systems that based on formal learning with the help of electronic resources nowadays. The prototype model is selected as the methodology for developing this application. The application is developed using Android Studio 162.4 software with Java programming language and Firebase database. Users for this application are divided into two where the main user of this application, students and administrators. Some of the modules that provided by this application are the login and registration module, note module, exercise module, quiz module, and report module. Hopefully, with this application is successfully developed it can help users in understanding the basic subject of object-oriented programming concepts.